Analysis of Ziswaf, Production Index and Sharia Stock Index on Economic Growth - Purbawati Setyaningsih; Roikhan Mochamad Aziz; Puji Hadiyati (The Indonesia Capital Market Institute, 2019)
This study analyzes the influence ZISWAF, Gini ratio, the total export value, the index of industrial production, sharia stock index investment to GDP growth, in the short and long term. Qualitative data were taken from BPS, Baznas, ACT Global Waqf, the FSA from March 2006 until December 2017 using the methodology of The Error Correction Model (ECM). The results of this study indicate that the variable Gini Ratio, Ziswaf, Total exports, Production Index and Sharia Stock Index on GDP economic growth have significant and positive effects in the long term and the short term. Meaning that these variables have a relationship with GDP economic growth. If the variable decreases or slows down-then GDP economic growth also. While total exports have insignificant effects and negative effects on GDP economic growth. The R-square regression value of the long-term model produces a proportion of 96 percent, the short-term model produces a proportion of 97 percent. Both in the long-run and short-run models, the highest coefficient value is the value of the Gini ratio with 4.941522 and 0.348043. All positive coefficients, Gini ratio variables, ziswaf and production index have a significant effect on gdp, total exports and sharia stock indexes do not have a significant effect on gdp both in the long and short-term models. It implies in the future, fiscal economic policy makers to economic growth that opened a lot of employment, by encouraging resource based economic activities of Indonesia's largest export-oriented agriculture and mining. Good Corporate goverment should do so gini ratio of the areas surrounding the economy improved and people kesejahtaeraan increase.